Chemical and mechanical strains tuned dielectric properties in Zr-doped CaCu3Ti4O12 highly epitaxial thin films. Issue 113 (30th October 2015) - Gao, M.; Feng, D.; Yao, G.; Zhang, Y.; Chen, C.-L.; Lin, Y.
Abstract : The dielectric properties of CaCu3 Ti4 O12 highly epitaxial thin films were successfully tuned by the in-plane strain. Abstract : The nature of strain tuned dielectric properties in CaCu3 Ti4 O12 (CCTO) films was systematically studied with chemical strain (various doping rates) and physical strain (different oxygen pressure treatments). Microstructural characterization revealed that the lattice parameters of the highly epitaxial CCTO thin films are strongly dependent upon both Zr doping rates and annealing oxygen pressures. Dielectric property measurements indicate that the dielectric loss can be tuned by optimizing the doping rate and annealing oxygen pressure. These findings indicate that the dielectric properties of CCTO can be manipulated by the in-plane strain achieved from either chemical or physical treatment.